Clinicopathological Correlation with Outcome of Diffuse Large B Cell Lymphoma: Experience in a Specialized Cancer Care Centre in Bangladesh (Journal of Medicine, 2021)
Background: Diffuse large B-cell lymphoma (DLBCL) is the most common type of non-Hodgkin lymphoma (NHL) in the world, and accounts for 30%–40% of all adult NHLs. It is clinically, morphologically and genetically a heterogeneous group of tumors composed of large B cells. This study aimed to determine the clinical features, treatment options, the response rate in a specialized cancer care centre.Methods: This retrospective study included all DLBCL patients registered in the department of Haematology of National Institute of Cancer Research and Hospital (NICR&H), Bangladesh between July 2016 to June 2019.Results: A total of 151cases were included in this study. The mean age was 47 years with a standard deviation (SD) of 15 years. Males (66.2%) were more in the occurrence of DLBCL. We divided the cases into three different entities of DLBCL and non-germinal centre B (non-GCB) variety was the prevalent (46.4%) one. Several types of first-line chemotherapy were used in management and the overall response rate (ORR) was 76.6% and 9.2% of death. The response was found to be significant with B symptoms, stage, and international prognostic index (IPI) score. But no significant difference was observed in outcome among different types of DLBCL after treatment.Conclusion: This retrospective study will help to ascertain the co relation of DLBCL outcome with clinicopathological profile. (edited)J MEDICINE JAN 2021; 22 (1) : 3-6